Forged Piston Delivers Higher Power and Torque in Jupiter Z: RCM II Mengidentifikasi Komponen GTG yang Kritis dan Strategi Pemeliharaan - Pahlewi, Muchamad Reysa; Fahruddin, Dr.A’rasy; Akbar, Ali; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Automotive development increasingly emphasizes component material selection and manufacturing methods to optimize engine performance. Specific Background: Pistons are critical engine components whose production route, particularly casting and forging, may influence power and torque characteristics. Knowledge Gap: Although many studies discuss piston materials and engine performance separately, direct comparative experimental evidence between casting and forged pistons under identical operating conditions on the Yamaha Jupiter Z 2007 remains limited. Aims: This study aims to analyze the differences in power and torque generated by standard, casting, and forged pistons using dynotest measurements at 2000, 4000, 6000, and 8000 RPM. Results: The results indicate that forged pistons produced the highest overall performance, with average torque reaching 13.32 Nm at 2000 RPM and average power reaching 11.2 HP at 6000 RPM. Casting pistons occupied an intermediate position, while standard pistons consistently produced the lowest values. At high engine speed, forged pistons maintained better performance stability than casting and standard pistons. Novelty: The study directly compares three piston types within the same motorcycle platform while also relating performance differences to piston mass variation, where forged pistons showed the lightest weight. Implications: These findings indicate that piston manufacturing type is closely associated with engine output, and forged pistons offer stronger potential for applications requiring higher power and torque performance. Keywords: Forged Piston, Casting Piston, Engine Performance, Power and Torque, Dynotest Key Findings Highlights Forged pistons produced the highest output across most engine speed ranges. Peak engine capability was observed around 6000 RPM before declining at 8000 RPM. Lower piston mass was associated with stronger high-speed performance stability.